Penetrating acoustic radiation – the reason of error building coordinate system - Карачун, Владимир Владимирович; Мельник, Виктория Николаевна (Eastern-European Journal of Enterprise Technologies, 2012)
The analysis of errors building the coordinate system in an aircraft with a three-axis gyro-stabilized platform with a gyroscopic sensor is carried out. The nature of their occurrence in the reverb space navigation equipment as a result of diffraction effects is developed